2006
DOI: 10.1590/s1516-35982006000800009
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfométrica de ovinos da raça Santa Inês criados nas microrregiões de Teresina e Campo Maior, Piauí

Abstract: RESUMO -Objetivou-se com esta pesquisa caracterizar fenotipicamente (peso e morfometria corporal) a conformação zootécnica de ovinos Santa Inês, machos e fêmeas de diferentes idades, criados em Teresina e Campo Maior, Piauí. Foram utilizados dados de pesos e de medidas corporais de 1.113 animais criados a campo e de 824 animais que participaram de exposição em feira agropecuária de Teresina. As características estudadas, comparadas pelo teste de Student-Newman-Keuls, foram: peso do animal, altura na cernelha e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 8 publications
(6 reference statements)
5
19
0
12
Order By: Relevance
“…Medium positive correlations were found between the biometric measurements and between these measures and body weight. This is in agreement with results obtained in sheep and cattle by , Rocha et al (2003) andCosta Júnior et al (2006). The correlation between RW and days on treatment was negative (-0.43), showing that this decreased with time, probably due to the use of fat for growth.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Medium positive correlations were found between the biometric measurements and between these measures and body weight. This is in agreement with results obtained in sheep and cattle by , Rocha et al (2003) andCosta Júnior et al (2006). The correlation between RW and days on treatment was negative (-0.43), showing that this decreased with time, probably due to the use of fat for growth.…”
Section: Resultssupporting
confidence: 93%
“…Costa Júnior et al (2006) found differences in rump width (19.6±2.4 cm), which was 6% higher in males. Cunha et al (2000), in an experiment with Santa Ines lambs slaughtered at 32 kg, found a hip width of 19.1 cm.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Morphometric measurements were performed with the help of a tape measure, with the animal standing correctly on its feet and legs, in agreement with the methodology described by Costa Júnior et al (2006). The following morphometric measurements were recorded: height, measured between the highest point of the interscapular region (withers) and the ground; body length, measured from wither to the tail insertion; and heart girth, measured on the external circumference of the thoracic cavity, on the axillae.…”
Section: Methodsmentioning
confidence: 99%
“…The Santa Ines is the most popular local breed of Brazil characterized by high adaptive value, reproductive, resistance to gastrointestinal parasites in addition to a good weight development in the tropics (COSTA JÚNIOR et al, 2006). It has been used as maternal lineage at the crossing with specialized breeds in meat production by is adapted the climatic conditions in the tropics.…”
Section: Introductionmentioning
confidence: 99%